(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides a philosophical analysis of the philosophical heritage of Central Asian thinkers of the First Renaissance and their role in the development of society. Central Asia became one of the major centers of culture during the First Renaissance, and its representatives made their worthy scientific and intellectual contributions to world civilization. The works and views of the thinkers on science are briefly analyzed.